2020
DOI: 10.1177/2050312120958897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacokinetic/pharmacodynamic ratio on tigecycline clinical response and toxicity in critically ill patients with multidrug-resistant Gram-negative infections

Abstract: Introduction: The information about the pharmacokinetics and optimal dose of tigecycline in critically ill patients with severe underlying diseases is limited and controversial. In this study, we evaluate the pharmacokinetic parameters of tigecycline in critically ill patients with multidrug-resistant Gram-negative infection and explore the association between the pharmacokinetic/pharmacodynamic ratio and treatment response. Methods: A prospective study was designed including critically ill patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Fan et al 16 reported that the hepatotoxicity of tigecycline was observed in 28.9% (11/38) of patients in the ICU. 16 In the study reported by Ruiz et al 15 elevated bilirubin and liver enzymes were observed in 20% of patients treated with tigecycline, and only elevated bilirubin was observed in 12% of patients. 15 In the present study, the incidence of tigecycline-associated hepatotoxicity was 33.8%.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Fan et al 16 reported that the hepatotoxicity of tigecycline was observed in 28.9% (11/38) of patients in the ICU. 16 In the study reported by Ruiz et al 15 elevated bilirubin and liver enzymes were observed in 20% of patients treated with tigecycline, and only elevated bilirubin was observed in 12% of patients. 15 In the present study, the incidence of tigecycline-associated hepatotoxicity was 33.8%.…”
Section: Discussionmentioning
confidence: 91%
“…16 In the study reported by Ruiz et al 15 elevated bilirubin and liver enzymes were observed in 20% of patients treated with tigecycline, and only elevated bilirubin was observed in 12% of patients. 15 In the present study, the incidence of tigecycline-associated hepatotoxicity was 33.8%. Our result was consistent with the result from Fan et al 16 Evaluating hepatotoxicity in critically ill patients treated with tigecycline is challenging due to various factors (such as underlying diseases, the severity of infection, and the use of other potentially hepatotoxic drugs).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the treatment was hardly successful because of the low blood concentrations when tigecycline was used in monotherapy. 30 Adverse events, such as hypofibrinogenemia, also resulted in treatment termination associated with tigecycline therapy. 31 In addition, nephrotoxicity and unclear dosing also limited the widespread clinical usage of polymyxin B.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large proportion of critically ill patients with multidrug-resistant GN infection are treated with tigecycline and do not achieve an appropriate pharmacokinetic and pharmacodynamic value. Even, tigecycline seems to be associated with hepatobiliary disorders in the critically ill population [19]. Fosfomycin has a very unique mechanism of action against Gram-positive and GN bacteria.…”
Section: Table 5 Outcomesmentioning
confidence: 99%